Efektivitas Model Problem Based Learning Berbantu Kartu Soal Terhadap Pemahaman Konsep Siswa SMK - Zuhri, Muhammad Saifuddin; Rizalenti, Estin Agisara (Universitas PGRI Semarang, 2026)
Conceptual understanding reflects the depth of students' comprehension of the meaning and underlying principles of a learning topic. Enhancing students' conceptual understanding is therefore a critical aspect of the teaching and learning process. This study aimed to examine the effectiveness of the Problem-Based Learning (PBL) model assisted by question cards in improving the conceptual understanding of vocational high school students. The research employed a quasi-experimental design conducted at SMK Swadaya Semarang, involving two groups of students who received different instructional treatments. The sample was selected using cluster random sampling. Data were collected through an essay-based written test designed to assess students' conceptual understanding of statistics. Data analysis was performed using an independent-samples t-test after fulfilling the prerequisite assumptions of normality and homogeneity. The normality test was conducted using the Shapiro–Wilk test, while the homogeneity of variance was examined using Levene's Test. The results indicated a statistically significant difference between the experimental and control groups sig = 0,000 0.001 and tvalue = 5,829 with tcritical = 1,994 so tvalue tcritical leading to the rejection of the null hypothesis. Furthermore, the experimental group achieved a higher mean score (86.67) than the control group (83.33). These findings demonstrate that the implementation of the Problem-Based Learning model assisted by question cards is effective in enhancing students' conceptual understanding of statistics among Grade 10 vocational high school students